Livestock Revolution and Its Impacts on the Sustainability of Marginal and Small Farmers in India: A Case Study - Khan, Nizamuddin; Iqubal, Asif (Journal for Geography, 2010)
Livestock husbandry is an important segment of Indian agriculture. Its share of contribution to agricultural gross products has increased since the implementation of the globalization of agricultural trade. Livestock revolution has occurred not only in India, but in all tropical deve-loping countries, owing to recently increasing demand for animal-derived products in national and international markets. We selected Aligarh, a micro geographical unit from the Upper Ganga plain of Uttar Pradesh for this study. 600 households from 12 villages in the area were surveyed for collection of data. The study revealed that the region witnessed growth in livestock husbandry with selected species during 1993-1994 to 2003-2004. Buffalo and goats showed a positive change due to enhancement in the demand of milk and meat on account of increasing urban consumers, liberalization of agri-business and the changing of food habits over the decades. Cattle numbers have contracted owing to the mechanization of agriculture and the prohibition of cow slaughter in the country. Two thirds of livestock keepers, workers and beneficiaries are poor farmers with less than 3 hectares of land holding. The majority of them follow the livestock-cropping integrated farming system, which is highly beneficial rather than rearing livestock exclusively. Livestock husbandry is an economically viable, socially acceptable and environmentally sustainable farming system in the study area of the Aligarh district.